SOSIALISASI MATEMATIKA REAKREASI PADA PESERTA DIDIK TINGKAT SD DAN SMP DI DUSUN PAOWAN UNTUK MENINGKATKAN MOTIVASI DAN MINAT BELAJAR MATEMATIKA - Zainul Munawwir; Lisma Dian Kartika Sari; Nur Hasanah; Intan Tri Utami; Moch. Shalehhudin (STKIP PGRI SITUBONDO, 2022)
It is well known that many students do not like mathematics because they lose that mathematics is difficult to learn. The impact of the Covid-19 pandemic has caused the teaching and learning process in schools to be diverted to using online methods such as Whatsapp, Google Classroom and others.Online learning or learning systems are considered less effective, because students have difficulty understanding subject matter, especially mathematics. In addition, students underestimate this online learning system as a result, sometimes they forget the assignments given by their teacher/lecturer and tend to use their free time by playing rather than studying. There are also cases where students cannot participate in online learning activities because they do not have facilities such as mobile phones, laptops or computers. This situation is usually experienced by students who live in remote villages and often the internet network in the village is still weak due to hampered learning activities. This condition causes the motivation and interest in learning mathematics to decrease significantly. The service team has held community service activities (PKM) with the theme